The relationship between navigation abilities and mental disorders: Poster - Hatamian, Nikki; Woodry, Robert; Tranquada-Torres, Bailey; Yee, Andre; Chrastil, Elizabeth (University of Latvia, 2021)
This study examined the relationship between aspects of navigational ability and behavioral traits associated with various mental disorders. We propose that navigational ability may utilize the same brain circuitry that has dysfunction in certain mental disorders and may be a beneficial early marker for these disorders. This study was inspired by the Research Domain Criteria (RDoC), a framework outlined by NIMH to study the basic dimensions of functioning that span the range of behavior from normal to abnormal. For example, we hypothesized that spatial perspective taking, which is important for navigation, could be associated with social perspective taking in disorders such as autism spectrum disorder or eating disorders. To test this question, participants recruited online through Amazon Mechanical Turk (n>200) completed two web-based spatial cognition tasks and a self-report measure of navigational ability. They also completed a battery of standardized questionnaires to capture non-pathological ranges of mental disorders. The Open Field Task (OFT) is similar to a virtual Morris water maze. It tests an individual’s ability to recall, locate, and navigate to four hidden objects scattered in an open field environment from a first-person perspective. The Spatial Orientation Task (SOT) tests spatial perspective taking by imagining different viewpoints in a layout of objects. The Santa Barbara Sense of Direction Scale (SBSOD) is a self-report measure of navigational ability. The behavioral questionnaires assessed pathological and non-pathological levels of mental disorders such as depression, anxiety, autism, and schizotypy to examine individual variability within the healthy population. Preliminary correlations indicate relationships between navigational ability and several mental disorders. In particular, obsessive-compulsive disorder and impulsivity showed relationships with performance errors in the SOT. These preliminary results also identify relationships between apathy as well as eating disorders and errors in the OFT. Together, these findings suggest that the circuitry for navigation and certain mental disorders could overlap, leading to new avenues for understanding these disorders.
Keywords: hippocampal subfields; memory; spatial navigation; structural MRI